KETERAMPILAN MENGAJAR GURU PAI PADA GENERASI DIGITAL - Ahmad Fahroni; Moh. Safiil Anam (Program Studi Pendidikan Agama Islam UNU Purwokerto, 2023)
The digital generation is a group of ages who from an early age have accessed and utilised digital technology as part of their daily lives (digital native), including influencing teaching and learning practices. This generation has unique characteristics such as a realistic attitude, has a high tolerant spirit, prefers to work together rather than receive orders from superiors, thinks pragmatically in solving the problems it experiences, is independent, assertive, emotional, intellectually expressive, has high curiosity, by questioning everything, innovative, lifelong learning. This certainly requires teachers to have competencies that are in accordance with the needs of the learners to be able to achieve the expected learning objectives.